The Effect of Arm Muscle Power Training on Long Service Skills in Extracurriculer Badminton Games - Jufrianis, Jufrianis; Fajri, Farhan; Luthfi, Amir (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This research is motivated by the fact that the long service skills performed by extracurricular student at SMA Negeri 2 Bangkinang Kota are not optimal and lack precision in their execution. The long service is the first stroke in the game of badminton and is considered part of the small ball sports category. Arm muscle power training is method to strengthen the arms using two exercises: push-ups and dumbbell higg swings, making it an effective method to improve long service skills. The research aims to determine the influence of arm muscle power training on long service skill. The research methodology employed in this is pre-experimental with a One Group pre-tets and post test design. Data was collected through purposive sampling with inclusion and excluxion criteria resulting in a sample size of 20 individuals. Data analysis utilized the Wilcoxon test and paired Sample T-test. Based on the statistical output “Test Statistics” it was found that the Asymp.Sig (2-tailed) value is 0.000. since 0.000 is less than < 0.05, it can be concluded that there is a significant difference between the pre- test amd post-test scores.in conclusion, this research demonstrates significant deifference between the pre-test and pos-test scores.in conclusion, this research demonstrates a significant influence of arm muscle power training on long service skills among extracurricular students at SMA Negeri 2 Bangkinang Kota.